Penerapan Model TAI (Team Assisted Individualization) untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas IV SD Negeri 091287 Panei Tongah Tahun Ajaran 2018/2019 - Ficha Aulia Nanda (Departement of Mathematics Education, 2021)
This study aims to determine the results of learning Mathematics using the TAI (Team Assisted Individualization) model. To find out whether there is an increase in student Mathematics learning outcomes through cooperative learning with the TAI (Team Assisted Individualization) model in class IV students at SD Negeri 091520 Hataran Jawa Academic Year 2018/ 2019 The subjects of this research were 33 grade IV students at SD Negeri 091520 Hataran Jawa. Research data on learning outcomes were collected using tests, and teacher activity data were collected using observation sheets. Before the action was taken, the level of completeness of student learning was 9.38% (3 out of 32 students completed) In cycle I, after the action was taken, the level of completeness increased to 65.63 % (and 32 students who completed were 21 people) In cycle II after carrying out further actions as a result of reflection on cycle 1 the level of completeness increased to 87.50% (of 32 students it was stated that they had completed as many as 28 people) Student activities in participating in learning after good actions were taken in cycle 1 and cycle II which increased. This was indicated by the frequency of attendance of students participating in Mathematics lessons getting better, from 91% attendance in cycle 1 rose to 99% in cycle II. Furthermore, students were motivated to take part in Mathematics learning. So it can be concluded that the results student learning has increased ie to 80.31 with the high category.